Directionality based Location Discovery Scheme Using Beacon Nodes with Transmission Capabilities throughout Sensor Network - Qinli An; Jianfeng Chen (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In this paper, we propose a range-free localization scheme for wireless sensor networks (WSNs) using four beacon nodes(BNs) equipped with a directional antenna with special transmission capabilities for sending wireless beacon signals throughout the sensor network. Each beacon node rotates with a constant angular speed and broadcasts its angular bearings. A sensor node can determine its location by listening to wireless transmissions from the four ﬁxed beacon nodes. The proposed method is based on an angle-of-arrival estimation technique that does not increase the complexity or cost of construction of the sensor nodes. We present error analysis and the best positions of beacon nodes in the proposed method. Numerical results, obtained by simulating several scenarios, show that the algorithm can reach a good level of convergence. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2705